Develop PF Mobile Application for Botany Catalogue - Luan, Shengyi (2015)
The mobile application is popular tool to apply in human life. If mobile application apply to botanic garden, it will convenient for botanical staffs. Because staffs did not need to record botany data in notes or store it in computer any more. They can store botany data in mobile phone and upload through internet server; also can retrieve data from internet sever. This mobile application includes four functions, first is catalogue for botany garden, users can view information and picture of plants. Second is Database for saving and editing the plant’s information. Third is QR code, use it for scan QR code of botany, and then botanical staff can get information of botany. The forth is hardware, this hardware use with Arduino and LCD, users use the mobile application send short message to Arduino board through Bluetooth, then LCD will display message for taking short notes.